Experimental Study of 10 kW Capacity Fin and Tube Heat Exchanger with Air and Water as Working Fluids - ADI KUSUMA (NIM 13103121), RENDRA
Heat exchanger is a device for exchanging energy between hot fluids and cold fluids and is used for a wide range of applications. One of the many applications is in solar energy technology. Today, a food drying process using solar energy has developed. In food drying system, a heat exchanger is needed to supply hot air for the drying process. For this purpose a design of a heat exchanger with specific capacity should be made. In this final project a set up and processing of an experiment for a fin and tube heat exchanger with specification uncontinues finned flat tube surface 11.04-0.486 is prepared. The heat exchanger is then tested to find it's certain characteristics. This test is the first step in a heat exchanger design process, which will be used in food drying system using solar energy. In this final project there will be two experiments. The purpose of the first experiment is to find the characteristics of a fin and tube heat exchanger which will be used in a drying process. Characteristic that we want to find is the relation between the Reynolds number of air with the Colburn factor J. The second experiment is done to know the relation between the value of e-NTU (effectiveness-Number Transfer Unit) for a certain ratio of Cmin/Cmax in a heat exchanger model in a certain work condition. The result of the first test will be a graphic of the Reynolds number in relation to the Colburn factor J. This graphic is then used for further design of a heat exchanger used in food drying process. The second test will result a graphic that shows correlation between e value and NTU for test heat exchanger. And this graphic expected to be used for heat exchanger practical design based on test heat exchanger.